Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Kimia pada Materi Persamaan Laju Reaksi dan Faktor-Faktor yang Mempengaruhi Laju Reaksi - Nuril Hidayatul Khuma'iroh; Rodi Edi (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to determine the effect of the Discovery Learning model on students' learning outcomes in the topic of Reaction Rate Equations and Factors Affecting Reaction Rates at SMA Srijaya Negara Palembang. The research employed a quantitative approach using a quasi-experimental method with a pre-test and post-test design involving two groups: an experimental class and a control class. The results showed an increase in learning outcomes in both classes. The average score in the experimental class increased from 39.41 to 59.70, while in the control class it increased from 43.70 to 53.70. However, the Mann-Whitney test yielded a significance value of 0.123 (p > 0.05), indicating no statistically significant difference between the experimental and control classes. Thus, the Discovery Learning model has not been proven to have a significant effect on students' learning outcomes compared to the conventional Direct Instruction model. Nevertheless, the increase in scores in the experimental class suggests that this model still holds potential to enhance student engagement and understanding. Therefore, Discovery Learning may be considered as an alternative strategy in teaching chemistry topics that require active student participation